ATLANTIS IN SPAIN VI - Papamarinopoulos, S.P (Bulletin of the Geological Society of Greece, 2010)
Plato described the end of Atlantis very vividly in a single day and night due to earthquakes and floods and nobody believed him because all experts imagined the impossibility of the giant island’s continental size in the middle of the Atlantic Ocean to vanish in 24 hours. They did not care to understand that Plato meant three different geographic and geological entities all called by him Atlantis which were the giant island, the horseshow basin and the concentric rater. Following Plato’s text that giant island was identified as the peninsula of Portugal-Spain and its northern extend. They did not even care to interpret correctly a genuine myth’s kernel which belonged in the end of the Bronze Age considering the island’s change of meaning versus time from prehistory to history both for the Egyptian and the Greek language up to Solon’s visit in Egypt in the 6th century B.C. This, mentioned above negligence, produced delay in understanding a complex problem which required a very good geological background besides other trans-scientific knowledge in archaeology, philology, mythology and mathematics in order to be faced properly. The loss of a nature made multi-ringed crater, which Plato also called Atlantis, in Andalusia’s palaecoast in the end of the Bronze Age due to earthquakes, a tsunami and land slide constitutes the end of Atlantis.